Advanced listening comprehension : developing listening and note-taking skills - Dunkel, Patricia. 4 0 16; Pialorsi, Frank; 5 (Rowley, MA : Newbury House Publishers, 1982)
Introduces the fundamentals of listening and note-taking using written exercises and audio activities.
Keywords: 2 -- 0; 6; Textbooks for foreigners.;Textbooks for foreign speakers. -- English language;Note-taking.;Listening.;English language;Listening.;Note-taking. -- 20; 20; 2